2015
DOI: 10.1109/tdei.2015.004793
|View full text |Cite
|
Sign up to set email alerts
|

Thermal-fluid characterization of alternative liquids of power transformers: A numerical approach

Abstract: The transformers lifespan depends importantly on its refrigeration. Mineral oils perform this work in the majority of the power transformers. However, this type of coolant has two main drawbacks: low biodegradability and low ignition point. Several alternative liquids are being developed in order to overcome these drawbacks. This paper compares their thermal-fluid behavior with a mineral oil by means of several parameters, such as temperature, flow rate, fluids velocity, convective heat transfer coefficient (h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 20 publications
1
27
0
Order By: Relevance
“…In 2015 Park et al [17] employed a 2D CFD model in order to obtain temperature and velocity profiles of some alternative liquids used in a distribution transformer of 2.3 MVA and a power transformer of 16.5 MVA. In the same year, Lecuna et al [18] carried out a 3D CFD simulation of an ONAN distribution transformer comparing a natural ester, a synthetic ester, a high kinematic viscosity silicone oil and a low kinematic viscosity silicone oil with a mineral oil. These works conclude that alternative liquids produce higher temperatures in the transformer windings designed for mineral oil.…”
Section: Introductionmentioning
confidence: 99%
“…In 2015 Park et al [17] employed a 2D CFD model in order to obtain temperature and velocity profiles of some alternative liquids used in a distribution transformer of 2.3 MVA and a power transformer of 16.5 MVA. In the same year, Lecuna et al [18] carried out a 3D CFD simulation of an ONAN distribution transformer comparing a natural ester, a synthetic ester, a high kinematic viscosity silicone oil and a low kinematic viscosity silicone oil with a mineral oil. These works conclude that alternative liquids produce higher temperatures in the transformer windings designed for mineral oil.…”
Section: Introductionmentioning
confidence: 99%
“…In 2015, Park et al employed a 2D-CFD model to obtain temperature and velocity profiles of some alternative liquids used in a distribution transformer of 2.3 MVA and a power transformer of 16.5 MVA [15]. In the same year, Lecuna et al carried out a 3D-CFD simulation of an ONAN distribution transformer comparing a natural ester, a synthetic ester, a high kinematic viscosity silicone oil and a low kinematic viscosity silicone oil with a mineral oil [16]. These works conclude that alternative liquids produce higher temperatures in the transformer windings designed for mineral oil.…”
Section: Simulation and Modelling Of Electrical Insulation Weaknessesmentioning
confidence: 99%
“…With these two equations, Eqs. (16) and (17), there are three variables that are volume oil flow Q o , bottom-oil temperature T Ob and top-oil temperature T Ot . Eq.…”
Section: Complete Loop Modellingmentioning
confidence: 99%
“…Several works have studied the cooling capacity of alternative dielectric liquids in comparison with that of mineral oil, [1][2][3]. However, the authors of this work have not found many articles in the scientific literature in which the impact of the insulation system aging on the cooling capacity of the liquid have been studied.…”
Section: Introductionmentioning
confidence: 99%